The Effective Methods of Strengthening Labor Management in Construction Enterprises - Wu, Di (Journal of Theory and Practice of Management Science, 2023)
Labor management is an important content of construction management system, which has an important influence on project construction efficiency and quality, and runs through construction management work throughout, but at present does not form a perfect and mature management mechanism, which leads to labor management still has problems and deficiencies. To this end, the paper explores the problems existing in the labor management of construction enterprises, and analyzes effective management methods in view of the problems, so as to improve the quality and effect of labor management.